Influence of Nordic walking on the physical condition of NTU «KhPI» students - Liubov Azarenkova (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine the impact of Nordic walking on the physical condition of students in the process of educational and health activities. Material and methods: analysis of scientific and methodological literature and regulations on the organization of physical education at the Department of Physical Education at NTU «KhPI» , express assessment of the physical condition of students by V.I Belov [1], student survey. The surveyed group consisted of 45 students of NTU «KhPI» humanities specialties of the Faculty of Social and Humanitarian Technologies, which belong to the main medical group. Results: the article analyzes the main forms of organization of educational and health activities of the discipline of physical education, determines the level of physical condition of female students before and after Nordic walking. Analyzing the results of the primary indicators of physical condition, the students were asked to practice Nordic walking to improve their physical condition. Classes were held for 10 weeks 3 times a week, where each week had its own focus. According to the results of the study, recommendations were given for the introduction of Nordic walking in the discipline of «Physical Education» NTU «KhPI». Conclusions: physical condition testing. Therefore, it is possible to propose to introduce Nordic walking into the educational process of the discipline of physical education.